Hydrogel-Based Enzyme and Cofactor Co-Immobilization for Efficient Continuous Transamination in a Microbioreactor - Menegatti, Tadej; Žnidaršič-Plazl, Polona (Frontiers in Bioengineering and Biotechnology, 2021)
A microbioreactor with amine transaminase co-immobilized with cofactor pyridoxal phosphate (PLP) was developed to enable efficient continuous transamination. The enzyme and a cofactor were successfully retained inside a porous copolymeric hydrogel matrix formed within the microreactor between two plates. After 10 days of continuous operation, minimal loss in reactor productivity was observed and no leaching of PLP or enzyme from the hydrogel was detected. The microbioreactor with immobilized cofactor showed similar performance with and without exogenous addition of PLP, which indicates no need for PLP addition during the process. Considering the time- and cost-efficiency of the immobilization procedure and the possibility of a numbering-up approach to achieve larger capacities, such a system shows high relevancy for industrial-scale application.